Evaluating Food Intake of Post-Acute Myocardial Infarction Patients According to a European Guideline and Mediterranean Diet Score: DICA-NUTS Substudy - Rodrigo Damasceno de Oliveira; Lívia Costa de Oliveira; Marcio Santos Prazeres; Tais Saint Martin Fonseca; Aline Marcadenti; Angela Cristine Bersch-Ferreira; Rachel Helena Vieira Machado; Elisa Maia dos Santos; Annie Seixas Bello Moreira; Grazielle Vilas Bôas Huguenin (Life, 2025)
Contextualization: Lifestyle changes, such as smoking cessation, physical activity, and healthy eating, are essential for the treatment and prevention of cardiovascular diseases. The 2021 update of the European Society of Cardiology (ESC) guidelines highlights the need to investigate the adherence to the Mediterranean diet in patients who have suffered acute myocardial infarction (AMI). Objective: The aim of this study was to investigate the adherence to the Mediterranean diet and dietary 2021 ESC guidelines of individuals who have suffered AMI and to evaluate the sociodemographic and lifestyle factors associated with the adherence. Methods: A cross-sectional study was conducted using baseline data from participants prior to enrollment in the DICA-NUTS multicenter clinical trial. The dietary intake was assessed using a food frequency questionnaire and 24 h dietary recall. The nutrient intake was compared with the nutritional recommendations of the 2021 ESC guidelines, and the adherence to the Mediterranean diet was analyzed using a Mediterranean diet score. Furthermore, the analyses of the factors associated with the Mediterranean diet score and 2021 ESC were performed. Analyses were conducted using Stata Data Analysis and Statistical Software version 15.0. Values were considered statistically significant when the p-value < 0.05. Results: Among 488 participants aged ≥ 40 years, moderate adherence to the Mediterranean diet was observed obtaining an average of nine points, with a low intake of vegetables, fish, and cereals. The protein intake was adequate with 18% (interquartile range [IQR] 15.0–23.1) of the total energy value, and the saturated fat intake was high with 9.7% (IQR 7.3–12.7) of the total energy value, while the carbohydrate and total fat intake was adequate. According to the 2021 ESC guidelines, the fiber intake was low with more than 79% of the sample consuming less than 30 g per day. The multivariate analysis using the 2021 ESC dietary recommendations showed that older age (≥60 years) [odds ratio (OR) = 1.63; 95% confidential interval (CI) = 1.44–1.91], never smoking (OR = 1.34; 95% CI = 1.17–1.65), and higher education (OR = 1.37; 95% CI = 1.17–1.77) were correlated with an increased fruit and vegetable intake. Non-white, never-smokers, and former smokers were more likely to consume fish. The alcohol scores were higher in older age participants and women. The dairy scores increased with older age, while the cereal scores decreased. No significant association was found for legumes. Conclusions: According to the scores used, the diet of these individuals moderately reflects the Mediterranean characteristics. Analyzing the 2021 ESC dietary recommendations, the studied population was inadequate. This study found different factors associated with an adequate food intake in post-AMI patients. The highlight of this study was that older age is more likely to increase fruit, vegetable, and dairy intake.